2017
DOI: 10.1159/000478009
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Adipose Tissue Graft to Treat Hypertensive Leg Ulcer: A Pilot Study

Abstract: Background: Adipose tissue is an abundant source of mesenchymal stem cells, called adipose-derived stem cells, which have anti-inflammatory and trophic effects to enhance overall tissue repair. Objective: To determine the healing effects of autologous adipose tissue graft on hypertensive leg ulcers. Methods: Prospective pilot study in 1 French dermatology department. Ten patients with a hypertensive leg ulcer were enrolled from April 2013 to June 2015. The primary end point was the wound closure rate at each f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The average reduction in wound area was 85.7% in the only study where this was reported. 27 The average time to complete wound healing ranged from 4 to 16 weeks in the 2 studies where this was reported. 24 , 27 …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The average reduction in wound area was 85.7% in the only study where this was reported. 27 The average time to complete wound healing ranged from 4 to 16 weeks in the 2 studies where this was reported. 24 , 27 …”
Section: Resultsmentioning
confidence: 98%
“… 22 The average number of wounds completely healed at primary follow-up was 65% (40%–100%); however, this was only reported in 3 studies. 19 , 24 , 27 In the 2 studies where partial healing of wounds was reported, this was achieved in 22% 19 and 60% 27 of cases. The average reduction in wound area was 85.7% in the only study where this was reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fat grafting has signi cant potential as a regenerative treatment in various diseases [3,4]. The therapeutic effect of fat grafting was also tested in scleroderma patients, identifying robust bene cial effects [5].…”
Section: Introductionmentioning
confidence: 99%